2009
DOI: 10.1080/09593330902911705
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen transfer in circular surface aeration tanks

Abstract: Surface aeration systems employed in activated sludge plants are the most energy-intensive units of the plants and typically account for a higher percentage of the treatment facility's total energy use. The geometry of the aeration tank imparts a major effect on the system efficiency. It is said that at optimal geometric conditions, systems exhibits the maximum efficiency. Thus the quantification of the optimal geometric conditions in surface aeration tanks is needed. Optimal geometric conditions are also need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The power number increases with increase in number of baffles, which can be explained by the increase in resistance offered by the increasing number of baffles. In oxygen transfer experiments four baffles were found to be optimal, so in further experiments four baffles were used 27…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The power number increases with increase in number of baffles, which can be explained by the increase in resistance offered by the increasing number of baffles. In oxygen transfer experiments four baffles were found to be optimal, so in further experiments four baffles were used 27…”
Section: Resultsmentioning
confidence: 99%
“…Rao and Kumar35 have shown that theoretical power per unit volume X ( = F 4/3 R 1/3 ) represents the small‐scale energy dissipation which occurs surrounding the impeller. This parameter was found useful in simulating the oxygen transfer rates of baffled and unbaffled surface aeration systems3, 27, 34, 36 The same parameter X may also be considered for simulating the power characteristics of baffled surface aerators.…”
Section: Resultsmentioning
confidence: 99%
“…The Rushton turbine produces radial flow and high shear rates near the impeller, which is important for air dispersion. Conditions of geometric similarity, i.e., √A/d=2.88, 24 and h/d=0.94, as suggested by Rao and Jyothish [20] were maintained in all the surface aerators.…”
Section: Measurementsmentioning
confidence: 99%
“…As excess treatment obligations are imposed, considerations for energy demand and conservations also increases through wastewater treatment plants (WWTPs). Furthermore, it has been estimated that the aeration process consumes more than half of the whole power requirements in WWTPs [3]. Therefore, increase of the gas-liquid oxygen transfer is considerably favorable for convenient energy utilization in wastewater treatment processes [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, surface aerators are more popular due to their ease of operation and comparative efficiency [3], [6]. Surface aerators are extensively used for the treatment of wastewater by biological oxidation.…”
Section: Introductionmentioning
confidence: 99%